Komunikasi Pemasaran Studio Foto melalui Media Sosial Instagram - Alsa Marwah; Yeni Yuniati (UNISBA Press, 2023)
Abstract. A photo studio is a place used by a photographer using a digital camera to be able to produce a photo with the addition of several tools available in the room. in this era of globalization, business in the field of photography is growing rapidly, especially in the photo studio business in the city of Bandung. The emergence of technological sophistication makes business people able to interact and communicate easily, especially in marketing communication. The existence of technological developments encourages social media as a medium in carrying out marketing activities, one of which is on social media Instagram. Instagram is a gathering place for people to interact with each other online and to promote, market, and sell certain products more easily. This research aims to find out the marketing communication of